Teaching strategy for introducing beginners to coherent states - Plastino, Ángel Luis (2019)
Handling coherent states by undergraduates students may be a hard task, as they have to deal with Glauber’s series e −(|α| 2/2) P∞ n=0 (α n / √ n!) φn(x). We show here that the task can be greatly simplified by introduction of a novel compact formula for Glauber coherent states employed in by Ferrary et al., This expression is obtained by solving the basic differential equation associated to coherent states a|αi = α|αi.